Secure Fit Co : cutscape tool / Muhammad Azrul Ramlan, Wan Afiq Adli Wan Ahmad Zuhaidi Shah and Muhammad Haziq Safiy Zulkiflee - Ramlan, Muhammad Azrul; Wan Ahmad Zuhaidi Shah, Wan Afiq Adli; Zulkiflee, Muhammad Haziq Safiy (2017)
Secure Fit Enterprise is a company that produce a unique rescue tools that can save hundred or thousand life from danger. Our company create tools, which is easy to use even in a panic situation or during disaster and emergency. We will establish our company at early - We created this company because in fact Malaysia has a high percentage of road accident and death. We want to educate our people how much valuable life is by having our product at that situation. Our target market are car users and rescue agency. We have targeted that our customer will buy our product because of its uniqueness and portability. Our product is very light and easy to use during emergency. We are very sure it will attract their attention to buy our product. The name of our product is Cutscape. The function of this product are it can help us escape from a trapped car by cutting the seatbelt and breaking the car window, It is very useful to save many life from death. The price also very cheap because of the low manufacturing cost. Even the cost is low, our company is very concern about the choice of the materials. We only choose strong and high quality material so the product will have high durability. We will market our product by selling it with a lowest price. RM 20.00 is an affordable price for the customers. Then, we will promote it using pamphlet and media social because it is the great platform to promote the business to worldwide.